Model Problem Based Learning (PBL) dan Project Based Learning (PjBL) terhadap Kemampuan Berpikir Kritis Siswa pada Pembelajaran IPA Kelas VII - Astuti, Asmi; Kashardi, Kashardi; Hartati, Merri Sri (Mahesa Research Center, 2026)
Critical thinking ability is one of the important competencies that need to be developed in science learning. However, learning that is still dominated by conventional methods causes students' critical thinking abilities to not develop optimally. This study aims to determine the differences in the effects of Problem Based Learning (PBL), Project Based Learning (PjBL), and conventional models on students' critical thinking abilities in science learning for grade VII at SMP Negeri 01 Lebong. This study is a quasi-experimental study with a Pre-Test Post-Test Control Group Design. The research sample was taken using a simple random sampling technique consisting of two experimental classes using the PBL and PjBL models and one control class using the conventional model. Data collection was carried out using an essay test to measure students' critical thinking abilities. Data were analyzed using the One Way ANOVA test. The results of the study showed a significant difference in students' critical thinking abilities in the three treatment classes. The Project Based Learning (PjBL) model was proven to be more effective in improving students' critical thinking abilities compared to the PBL and conventional models.